Humoresque: A Laugh on Life with a Tear Behind It - Hurst, Fannie, 1889-1968 (Salt Lake City, UT : Project Gutenberg, 2006)
"Humoresque: A Laugh on Life with a Tear Behind It" by Fannie Hurst is a novel that was likely written in the early 20th century. The narrative delves into the lives of immigrant families living in a bustling tenement on the Lower East Side of New York, particularly focusing on the Kantor family. The story captures the profound contrasts of life$1 (Bjoy and sorrow, hope and despair$1 (Bas the characters navigate their complex realities. At the start of the book, the reader is introduced to the Kantor family, highlighting their cramped living conditions and the dynamics of their daily life. The opening scene immerses us in the vibrant yet harsh environment of the Bowery, displaying a mosaic of cultures and challenges faced by the residents. We meet Mrs. Kantor, who is busy preparing for her son Leon's birthday, and we see the interactions between her and her children, especially the youngest, Leon, whose desire for a violin becomes central to the family's hopes and dreams. Through a mix of humor and tragedy, Hurst portrays the family's struggles and aspirations against the backdrop of a rapidly changing America, setting the stage for themes of ambition, sacrifice, and the pursuit of happiness. (This is an automatically generated summary.)s
Humoresque -- Oats for the woman -- A petal on the current -- White goods -- "Heads" -- A boob spelled backward -- Even as you and I -- The wrong pew.
Release date is 2006-02-01
Produced by Suzanne Shell, Charlie Kirschner and the PG Distributed Proofreaders
Keywords: Fiction; Short stories, American